2008
DOI: 10.1159/000148063
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic Microsampling to Analyze the Epithelial Lining Fluid of Patients with Pulmonary <i>Mycobacterium avium</i> Complex Disease

Abstract: Background: A new bronchoscopic microsampling (BMS) probe has recently been developed, which allows the minimally invasivecollection of epithelial lining fluid (ELF) simultaneously from multiple sites. While the number of immunocompetent patients with pulmonary Mycobacterium avium complex(MAC) disease is growing, the precise pathogenesis of the disease remains to be clarified. Objectives: This study aimed to measure biochemical markers in the ELF of patients with pulmonary MAC disease using BMS. Methods: We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The present study also demonstrated that for most of the cases with comorbid MACLD and lung cancer, the two diseases existed in the same lobe. In another study, analysis of the epithelial lining fluid revealed that the inflammatory reaction caused by MAC might spread to an unaffected area other than the original MAC-infected area [ 28 ]. Furthermore, attention has been paid to the Mendelian susceptibility to mycobacterial diseases, such as interferon gamma receptor deficiencies and impaired interleukin-2 production, although no data were presented here regarding this [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrated that for most of the cases with comorbid MACLD and lung cancer, the two diseases existed in the same lobe. In another study, analysis of the epithelial lining fluid revealed that the inflammatory reaction caused by MAC might spread to an unaffected area other than the original MAC-infected area [ 28 ]. Furthermore, attention has been paid to the Mendelian susceptibility to mycobacterial diseases, such as interferon gamma receptor deficiencies and impaired interleukin-2 production, although no data were presented here regarding this [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In facilities performing lung transplantation, it may be possible to collect epithelial lining fluid of the grafted lung by minimally invasive microsampling after the operation and measure Ecadherin in this fluid [24]. The serial monitoring of reperfusion injury by such a method may prevent complications after lung transplantation and allow early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ELF can be obtained by bronchoscopic microprobe sampling (BMP), a technique that uses small adsorptive probes . ELF collected in this way contains higher concentrations of biologically active molecules .…”
Section: Introductionmentioning
confidence: 99%
“…ELF collected in this way contains higher concentrations of biologically active molecules . Another advantage of microprobe sampling is that the locations from which ELF was obtained are clearly defined and it allows collection of ELF from both central and peripheral airways .…”
Section: Introductionmentioning
confidence: 99%